Crop and Livestock Labor Standards - Langemeier, Michael R.; Dhuyvetter, Kevin C. (My University, 2005)
Publication contains crop and labor standards developed to provide labor information for use in whole-farm and enterprise budgeting, forward planning, and comparative studies.
MF802_2005_10
Keywords: MF802; Economics; MF